Shiga Toxin Mediated Neurologic Changes in Murine Model of Disease - Pradhan, Suman; Pellino, Christine; MacMaster, Kayleigh; Coyle, Dennis; Weiss, Alison A. (Frontiers in Cellular and Infection Microbiology, 2016)
Seizures and neurologic involvement have been reported in patients infected with Shiga toxin (Stx) producing E. coli, and hemolytic uremic syndrome (HUS) with neurologic involvement is associated with more severe outcome. We investigated the extent of renal and neurologic damage in mice following injection of the highly potent form of Stx, Stx2a, and less potent Stx1. As observed in previous studies, Stx2a brought about moderate to acute tubular necrosis of proximal and distal tubules in the kidneys. Brain sections stained with hematoxylin and eosin (H&E) appeared normal, although some red blood cell congestion was observed. Microglial cell responses to neural injury include up-regulation of surface-marker expression (e.g. Iba1) and stereotypical morphological changes. Mice injected with Stx2a showed increased Iba1 staining, mild morphological changes associated with microglial activation (thickening of processes), and increased microglial staining per unit area. Microglial changes were observed in the cortex, hippocampus, and amygdala regions, but not the nucleus. Magnetic resonance imaging (MRI) of Stx2a-treated mice revealed no hyper-intensities in the brain, although magnetic resonance spectroscopy (MRS) revealed significantly decreased levels of phosphocreatine in the thalamus. Less dramatic changes were observed following Stx1 challenge. Neither immortalized microvascular endothelial cells from the cerebral cortex of mice (bEnd.3) nor primary human brain microvascular endothelial cells were found to be susceptible to Stx1 or Stx2a. The lack of susceptibility to Stx for both cell types correlated with an absence of receptor expression. These studies indicate Stx causes subtle, but identifiable changes in the mouse brain.